Fabrication of Carbon Nanodots/Platinum Functionalized Nanocomposite Hydrogel Formulation for Near‐Infrared Responsive Delivery of Doxorubicin to Promote Necroptosis for Mitigating Lung Cancer Cells: In Vitro Photodynamic Therapy - Xiaoqin An; Junjun Bai; Yuan Li (Macromolecular Materials and Engineering)
Abstract Lung cancer remains one of the deadliest cancers, marked by uncontrolled cell growth in the lungs and often diagnosed at later stages. This study presents a novel hydrogel‐embedded nanocomposite responsive to Near‐Infrared (NIR) light (CN‐Pt‐DOX@CS+NIR) to induce necroptosis in lung cancer cells. The composite, created by combining Carbon Nanodots (CNs), Platinum Nanoparticles (PtNPs), and Doxorubicin (DOX) within a Chitosan (CS)‐based hydrogel, demonstrated favorable properties for sustained drug release. Upon NIR irradiation, the CNs increase oxidative stress and initiate apoptosis due to the generation of reactive oxygen species (ROS) and caspase activation (3, 8, and 9). The PtNPs enhance ROS production and disrupt mitochondrial membrane potential (MMP), further promoting cell death. DOX, a well‐known chemotherapeutic, intercalates DNA and inhibits topoisomerase II, leading to apoptosis. These combined effects result in significant cytotoxicity under NIR stimulation, as shown in vitro on A549 and H1299 cells, confirmed through various assays including AO/EB and DAPI staining, flow cytometry, and RT‐PCR. Additionally, the hydrogel matrix provides a controlled release of the therapeutic agents and improves localized delivery. Combining CNs, PtNPs, and DOX with NIR enhanced in vitro cytotoxic effects, apoptosis, ROS generation, and potential for targeted lung cancer therapy.